Chemical Composition and Antimicrobial Activity of the Essential Oil of Artemisia absinthium Asteraceae Leaves. Issue 1 (2nd January 2017) - Vieira, Tatiana M.; Dias, Herbert J.; Medeiros, Talita C.T.; Grundmann, Carlismari O.; Groppo, Milton; Heleno, Vladimir C. G.; Martins, Carlos H.G.; Cunha, Wilson R.; Crotti, Antônio E. M.; Silva, Eliane O.
Abstract: This study reports on the chemical composition and antimicrobial activity of the essential oil from Artemisia absinthium L. leaves AA EO collected in Brazil against a representative panel of cariogenic bacteria. The minimum inhibitory concentrations MICs were determined by the broth dilution method in 96-well microplates. AA EO was inactive against most of the investigated oral pathogens, but it displayed moderate activity against Streptococcus mutans MIC = 250 μg/mL and very promising activity against Streptococcus mitis MIC = 62.5 μg/mL. Gas chromatography GC FID and gas chromatography mass spectrometry GC-MS revealed that camphor 1, 19.0 %, E -caryophyllene 2, 9.3 %, eucalyptol 3, 6.8 %, germacrene D 6.7 %, and α-cadinol 6.5 % were the major chemical constituents of AA EO. However, when tested alone, compounds 1, 2, and 3 were inactive MIC > 1000 μg/mL against all the studied microorganisms.